Hubungan Kelentukan Pinggang Dan Kekuatan Otot TungkaiTerhadap Keterampilan Servis Tekong Sepak Takraw Atlet Desa Suka Bumi Lebong Tengah - Soleha, Lola; Suwarni, Suwarni; Martiani, Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to determine the relationship between waist flexibility with leg muscle strength and the skill of serving tekong athletes of Suka Bumi Village, Lebong Tengah. The method used in this research is correlational quantitative method. The population in this study were tekong athletes of Suka Bumi Village, Lebong Tengah, Sepak Takraw Sports Branch, totalling 22 students, while the sample in this study were 22 students. The instruments in this study were the Waist Flexibility Test, Limb Muscle Strength and Takraw Service Test. The data analysis prerequisites used are normality test with Lilliefors and homogeneity test. The data analysis used is Product Moment Correlation analysis with a significance level of 5%. Based on the results of the study, it was found that there was a significant relationship between waist flexibility (X) and the results of takraw service skills as indicated by the value of r = 0.248.